2010
DOI: 10.1088/0004-637x/711/2/619
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Element Abundances in a Large Sample of Galactic Planetary Nebulae

Abstract: In this paper we present emission line strengths, abundances, and element ratios (X/O for Ne, S, Cl, and Ar) for a sample of 38 Galactic disk planetary nebulae (PNe) consisting primarily of Peimbert classification Type I. Spectrophotometry for these PNe incorporates an extended optical/near-IR range of λλ3600-9600Å including the [S III] lines at 9069Å and 9532Å, setting this relatively large sample apart from typical spectral coverage. We've utilized ELSA (Emission Line Spectrum Analyzer), a 5-level atom abund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 40 publications
8
61
0
Order By: Relevance
“…These objects, observed in 2003 and 2004 with the Kitt Peak National Observatory 2.1 m telescope or the Cerro Tololo Inter-American Observatory (CTIO) 1.5 m telescope, are listed at the bottom of Table 1. See Section 2 in Milingo et al (2010) for details on the instrumental configurations and observing procedures. These data were also analyzed in the standard fashion using IRAF, as outlined above.…”
Section: Kpno and Ctio Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…These objects, observed in 2003 and 2004 with the Kitt Peak National Observatory 2.1 m telescope or the Cerro Tololo Inter-American Observatory (CTIO) 1.5 m telescope, are listed at the bottom of Table 1. See Section 2 in Milingo et al (2010) for details on the instrumental configurations and observing procedures. These data were also analyzed in the standard fashion using IRAF, as outlined above.…”
Section: Kpno and Ctio Observationsmentioning
confidence: 99%
“…Figure 1 is a plot of 12+log(O/H) versus galactocentric distance (Table 6, Column 3) in kpc for the 124 objects in our PN sample with well-measured distances. The PN sample is a compilation of objects from Henry et al (2004), Milingo et al (2010), plus those objects reported upon for the first time in this paper (HK10). Our sample contains only those objects classified as either Type I or Type II, i.e., objects whose location and kinematics indicate that their progenitors were members of the disk population.…”
Section: The Determination Of the Oxygen Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang & Liu (2007) concluded that Ne and O production only occurs for 12+log(O/H)<8, below even the SMC, indicating that the first possibility is likely the correct one. references, see Milingo et al (2010). 6.3.…”
Section: Neonmentioning
confidence: 99%